Bone repair of critical size defects treated with autogenic, allogenic, or xenogenic bone grafts alone or in combination with rhBMP-2 - Issa, Joao Paulo; Gonzaga, Miliane; Kotake, Bruna Gabriela; Lucia, Conrado de; Ervolino, Edilson [UNESP]; Iyomasa, Mamie (Wiley-Blackwell, 2016)
ObjectiveTo evaluate the bone repair of critical size defects treated with autogenic, allogenic, or xenogenic bone grafts alone or in combination with rhBMP-2. Material and methodsIn 112 rats, a critical bone defect of 5mm bilaterally in the calvaria was made and filled with different bone grafts alone or combined with rhBMP-2: group autograft (AuG); group allograft (AlG); group xenograft (XeG); group AuG/BMP-2 (autograft and 5g rhBMP-2); group AlG/BMP-2 (allograft and 5g rhBMP-2); group XeG/BMP-2 (xenograft and 5g rhBMP-2); group BMP-2 (5g rhBMP-2); and control group, filled only with blood coagulum. After a period of 4 or 6weeks, the animals were euthanized. Histological and histometric analyses were performed for new bone formation (NB), as well as the immunohistochemical detection of tartrate-resistant acid phosphatase (TRAP), and zymographic analysis (MMP) of type 2 and 9. ResultsHistological analysis showed the bone healing process was faster and favorable in AuG and AuG/BMP-2. In both periods, the grafted groups (AuG, XeG and AlG) had a greater volume of NB than the control group, which was even greater when combined with rhBMP-2. The XeG group showed a higher number of TRAP-positive multinucleated osteoclasts, and enzymatic activity revealed different levels of proMMP-2, MMP-2, and MMP-9 (6weeks). ConclusionThe different types of grafts increased bone formation, mainly associated with rhBMP-2, enhancing and accelerating the repair process. These groups had higher enzymatic indices than the control group especially with XeG, which also showed higher TRAP-positive multinucleated cells similar to osteoclasts, suggesting a remodeling process.
Keywords: animal experiments; bone substitutes; growth factors; morphometric analysis; wound healing